PENERAPAN HUKUM PIDANA MILITER PADA KASUS TINDAK PIDANA DESERSI DALAM WAKTU DAMAI YANG DILAKUKAN OLEH TENTARA NASIONAL INDONESIA ANGKATAN DARAT DI AJENDAM I BUKIT BARISAN - Hana Oktaviana Fahlevi; Alvi Syahrin; Muhammad Hamdan; Edi Yunara (USU LAW JOURNAL, 2018)
ABSTRACT The Indonesian Army (TNI AD) is part of the Indonesian Armed Forces (TNI) that acts as a state instrument in the field of land defense. The main task of the Indonesian Army is to uphold the sovereignty of the state, to maintain the territorial integrity of the Unitary State of the Republic of Indonesia based on Pancasila and the 1945 Constitution, and to protect the entire nation and the entire Indonesian blood from the threats and disturbances to the unity of the nation and state. In carrying out its duties and obligations to the state, the Ajendam I /Bukit Barisan can not be separated by the problems. One of the problems encountered is the occurrence of desertion crimes committed by members of the Ajendam I / Bukit Barisan.The crime of desertion is a pure military crime committed by members of the Indonesian Armed Forces is an act in which a member of Indonesian Armed Forces leaves the unit/base without the legal permission of his superior. The settlement of desertion cases is processed through a special justice system that is military court. The method used in this research is juridical normative and empirical juridical which refers to the principles of law in the form of conception, norms, rules of legislation, court decision and collect, find data and information through field study to member of Indonesian Army of Ajendam I/Bukit Barisan who commits a criminal act of desertion in peace time. The nature of this thesis research is descriptive analysis. Data collection techniques conducted in this study is primary data collection conducted by field study and secondary data collection conducted by library research.   Keywords: Members of Indonesian Army, Desertion, Implementation of Military Criminal Law.